2016
DOI: 10.1007/s10509-016-2840-y
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic charged core envelope star

Abstract: We study a charged compact object with anisotropic pressures in a core envelope setting. The equation of state is quadratic in the core and linear in the envelope. There is smooth matching between the three regions: the core, envelope and the Reissner-Nordstr\"{o}m exterior. We show that the presence of the electric field affects the masses, radii and compactification factors of stellar objects with values which are in agreement with previous studies. We investigate in particular the effect of electric field o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Inspired from many previous revealed famous articles [78,79,80,81,82,83,84,85,86,87,88,89,90], we have taken static, spherical symmetric metric for this pulsar model. The Einstein field equations for the metric Eq.…”
Section: Interior Spacetimementioning
confidence: 99%
“…Inspired from many previous revealed famous articles [78,79,80,81,82,83,84,85,86,87,88,89,90], we have taken static, spherical symmetric metric for this pulsar model. The Einstein field equations for the metric Eq.…”
Section: Interior Spacetimementioning
confidence: 99%
“…In favour of anisotropy Kalam et al [26] have developed a star model and showed that central density depends on anisotropic factor. For recent investigations, there have been important efforts in describing relativistic stellar structure in [27][28][29][30]. The algorithm for solutions of Einstein field equation via.…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, in order to design the core envelope model, the Darmois-Isreali conditions should be satisfied at the junction of the core and the envelope. With this empirical aspect, many authors [1,[12][13][14][15][16][17][18][19][20][21][22] have developed stellar models, with an assumption of a core and an envelope, for highly dense relativistic objects. Eventually in most of the core-envelope solutions so far obtained have the continuity of only metric potentials and pressure at the junction of the core and the envelope.…”
Section: Introductionmentioning
confidence: 99%